2011
DOI: 10.1111/j.1600-0765.2010.01342.x
|View full text |Cite
|
Sign up to set email alerts
|

Potent anti-inflammatory effects of systemically administered curcumin modulate periodontal disease in vivo

Abstract: Background Curcumin is a plant-derived dietary spice with various biological activities, including anti-tumoral and anti-inflammatory. Its therapeutic applications have been studied in a variety of conditions, including rheumatoid arthritis, colon cancer and depression; but no studies evaluated the effects of curcumin on periodontal disease in vivo. Methods Experimental periodontal disease was induced in rats by placing cotton ligatures around both lower first molars. Curcumin was given to the rats intragast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
134
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(158 citation statements)
references
References 62 publications
(79 reference statements)
15
134
0
9
Order By: Relevance
“…In-vivo evaluation of curcumin in-situ gel In previous reports, the efficacy of curcumin to control dental diseases and inflammations has been proven after systemic or local administration (Guimarães et al, 2011;Rastogi et al, 2012). Curcumin's low systemic bioavailability can be overcome using a local drug delivery that allows the concentration of a particular drug at the desired site.…”
Section: Stability Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In-vivo evaluation of curcumin in-situ gel In previous reports, the efficacy of curcumin to control dental diseases and inflammations has been proven after systemic or local administration (Guimarães et al, 2011;Rastogi et al, 2012). Curcumin's low systemic bioavailability can be overcome using a local drug delivery that allows the concentration of a particular drug at the desired site.…”
Section: Stability Testingmentioning
confidence: 99%
“…It also enhances wound healing by causing an increase in fibronectin and transforming growth factor â transcription (Guimarães et al, 2011;Rastogi et al, 2012). Worth mentioning is that Curcumin has an antiadhesion effect against Streptococcus mutans on extracellular matrices and tooth surfaces, which are crucial receptors for dental caries and infective endocarditis (Song et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on curcumin has demonstrated a wide spectrum of therapeutic effects such as anti-inflammatory, antioxidant, antibacterial, antiviral, antifungal, antitumour, antispasmodic, hepatoprotective and wound healing properties. [13][14][15] The anti-inflammatory properties of curcumin can be useful in the treatment of inflammatory periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Another mechanism is by modulating the activity of signalling pathways and transcription factors, especially nuclear factor-jB (NF-jB), activating protein-1 (AP-1) and mitogen-activated protein (MAP) kinases. 15 In a recent study, curcumin effectively inhibited activation of NF-jB in the gingival tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation